2018
DOI: 10.1108/rbf-11-2016-0072
|View full text |Cite
|
Sign up to set email alerts
|

Can advisors eliminate the outcome bias in judgements and outcome-based emotions?

Abstract: Purpose An outcome bias occurs when performance is evaluated based upon the outcome of the decision rather than upon the quality of the decision itself. The purpose of this paper is to test experimentally whether advisors eliminating the uncertainty in the quality of decisions as a potential driver of the outcome bias can eliminate this bias in judgements. Additionally, the paper analyses whether such advisors can attenuate the emotional experience after decisions’ outcomes by supporting the cognitive understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Since it is crucial to understand how to enhance decision-making through strategies other than simply raising awareness, examining the factors that accentuate or attenuate outcome bias in self-evaluations could be a fruitful avenue for further research. As a notable exception in the context of self-evaluations, Bachmann (2018) shows that advising can eliminate outcome bias by reducing uncertainty in the quality of decisions, particularly after bad outcomes. Regarding third-party evaluations, et al ( 2016) find that outcome bias is reduced when participants evaluate an individual separately relative to when participants evaluate individuals jointly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it is crucial to understand how to enhance decision-making through strategies other than simply raising awareness, examining the factors that accentuate or attenuate outcome bias in self-evaluations could be a fruitful avenue for further research. As a notable exception in the context of self-evaluations, Bachmann (2018) shows that advising can eliminate outcome bias by reducing uncertainty in the quality of decisions, particularly after bad outcomes. Regarding third-party evaluations, et al ( 2016) find that outcome bias is reduced when participants evaluate an individual separately relative to when participants evaluate individuals jointly.…”
Section: Discussionmentioning
confidence: 99%
“…Ratner and Herbst (2005) find that a negative emotional response resulting from the unfavorable outcome of a good decision may lead individuals to switch to inferior alternatives. Bachmann (2018) shows that advisers can eliminate outcome bias in the context of investment decisions, particularly after bad outcomes. However, the advisers are unable to prevent affective reactions after bad outcomes and instead might even reinforce them.…”
Section: Related Literaturementioning
confidence: 99%
“…Charles and Kasilingam (2015) found that lack of cognition, inexperience, and impetuosity lead to individuals’ emotional instability. Bachmann (2018), Bazley et al (2021), Peng et al (2011), and Sourirajan and Perumandla (2022) found that emotional behavior can impact the investment decision.…”
Section: Behavioral Biases and Investment Decision-makingmentioning
confidence: 99%